Analysis of the Difficulties Faced by Seventh Grade Students of Mts Al-Haq Margahayu in Mastering Listening (Maharah Istima') and Speaking Skills (Maharah Kalam) in Arabic Language Learning: English - Marlina, Lina; khairunnisa Hasugian (Universitas Djuanda, 2025)
The focus of this study was to evaluate the problems faced by the seventh grade students of MTs Al-Haq Margahayu in mastering the skills in Arabic language learning, ( maharah istima ) listening and ( maharah kalam ) speaking. Data were collected through direct observation and survey using a qualitative descriptive case study approach. The findings of this study showed students' difficulties such as limited vocabulary, accent variations, low self-confidence and lack of speaking practice were also the main challenges. The use of the book